An its gene-mediated molecular detection of fungi associated with natural and artificial agarwood from Aquilaria malaccensis - Aizi Nor Mazila, Ramli; Sufihana, Yusof; Bhuyar, Prakash; Aimi Wahidah, Aminan; Saiful Nizam, Tajuddin (Slovak University of Agriculture, 2023)
The current study examined fungal diversity in manufactured and natural agarwood samples perceived from A. malecensis trees in a plantation and the East Malaysia rainforest. Isolated fungi were also subjected to molecular analysis. The fungal community composition of healthy and damaged tree samples from both plantation and the wild forest was identified using PCR amplification of the internal transcribed spacer (ITS) region from fungal isolates. Meanwhile, ten groups of fungi isolates are expected to be placed in both natural and inoculated based on 1000 bootstrap values. They validated earlier genomic identification; 55 fungal isolates were discovered in artificial and natural agarwood, including agarwood and healthy wood. Ten fungal groupings were developed based on morphological characterization similarities. Based on NCBI BLAST analysis, molecular identification revealed Fusarium solani, Botryosphaeria theobromae, Polyporales spp, Schizophyllum commune, Aspergillus aculeatus, and Lasiodiplodia theobromae. Fusarium solani excelled in A. aculeatus and Polyporales spp. in agarwood samples and healthy wood. The presence of more fungi species in natural agarwood than in artificial agarwood may be due to the favourable humid and shaded habitat for fungal growth. Nonetheless, synthetic agarwood was able to synthesize agarwood-related chemical compounds. Considering F. solani was often identified in both agarwood, agarwood inoculant may act as a booster for F. solani to begin pathogenicity in artificial agarwood. The current research shows that artificial agarwood may provide quality comparable to natural agarwood and is not influenced by fungus interacting with the tree.